Collaboration, creativity and entrepreneurship in tourism: a case study of how design thinking created a cultural cluster in Dublin. (2017) - Robbins, Peter; Devitt, Frank
Tourism accounts for 7.3% of national employment in Ireland and tourists with a craving for culture, the 'culturally curious', are a key market-segment. Following Ireland's economic collapse, the national tourism agency has evolved its role from funding tourism infrastructure to facilitating collaborative innovation. This paper presents the revelatory case study of Merrion Square, a tourism local innovation system (TLIS) of mainly cultural organisations who collaborated using design thinking, which incorporated ethnographic research, involving customers, tour operators, historians and artists to develop a portfolio of entrepreneurial and novel ideas for enhanced tourism experiences. The result was a series of successful new enterprises and the development of a sustained higher level of cooperation between the institutions. 85% of the institutions involved report increased visitor numbers as a consequence. This paper makes a valuable contribution by establishing design thinking's role in collaborative, multi-sectoral tourism service innovation and entrepreneurship.